(untitled) (Journal of Innovative Solutions for Eco-Environmental Sustainability, 2025)
Hydrogen has recently attracted global attention as a Bioproduct due to its relevance to energy and health. While conventional dark fermentation research has mainly focused on genus Clostridium, several challenges remain, including contamination by non-target microbes and substrate limitations. In this lecture, we will present our recent advances in “Lactate-Driven Hydrogen Fermentation” using genus Megasphaera, a novel approach pioneered by our research group. This system enables anaerobic fermentation of lactate to produce hydrogen and short-chain fatty acids, allowing the use of non-sugar substrates and eliminating the need for thermal pretreatment, which has traditionally been required. We will also introduce our technical developments, such as rapid detection methods for Megasphaera species (PCR-RFLP and FISH) and improved process stability via co-cultivation with lactic acid bacteria. These findings redefine the microbial ecology of hydrogen fermentation and open new avenues for the biotechnological utilization of unused organic resources. We have maintained a long-standing friendship with Professor Karen Trchounian of YSU, and together we have actively explored possibilities for technological collaboration between our two countries. Through this work, I aim to bridge traditional fermentation science with next-generation bio-industries and challenge the future with innovation.